Informing realities: Research, public opinion, and media reports on migration and integration - Allen, W; Blinder, S; McNeil, R (Oxford University Press, 2019)
This chapter addresses how research and public debate about migration interact with and inform each other, focusing on public perceptions and media coverage as important aspects. Factors including generalized public innumeracy about migration levels, effects of emotions on perceptions, and variation in the perceived credibility of different messengers make communicating information— of which research evidence is an important type—a complex process with multiple points of potential resistance. Meanwhile, the demands and expectations of public users and policy-makers can influence how research happens and the types of questions that are seen to be more meaningful. These interrelationships exist within wider social, political, and economic contexts that, in certain circumstances, are likely to favour some outcomes over others. In total, the chapter argues that the pathway from generating research evidence to impacting public debates is not only uncertain, it is also more complex than is often presumed. Research on migration often aims to influence not only relatively specialized research communities, but also broader society including political institutions, policy processes, and media and public debates. Whether motivated by the intrinsic value of relating their work to the wider world, or prodded by shifting financial and professional incentives, academic researchers increasingly find themselves being asked to demonstrate how their work has impact beyond universities—especially when that research is publicly funded. Yet, defining and generating that impact is often elusive. Public debate and major policy decisions often seem to fly in the face of the evidence base accumulated by researchers in the academy, civil society, and even in government agencies themselves. Despite escalating pressure to produce impactful research, evidence-based public debate seems as far off as ever—particularly on the issue of immigration, where public discussion is often polarized, emotive, and based on perceptions rather than reality (Duffy 2014). In this chapter, we explore the relationships between research and public debate, two aspects of the tripartite model proposed in the Introduction to this volume. We argue that the idea of ‘research impact’ is often based on a naive model of one-way effects that does not reflect the multifaceted relationships between research and elements of public debate. The pathway from research evidence to public debate is not only uncertain, it is also inevitably bidirectional: media and public discussions affect research as well as being affected by it. As academics aim to have impact on public debate, they should acknowledge even further how their research—comprising the questions they ask, the methods they employ, and the modes and venues in which they present their (p.51) findings—relates to the contours of public debate. Therefore, despite growing expectations that research can and should influence public debate, the implicit model of impact underlying such expectations is misleading and simplistic.